2012
DOI: 10.1177/000348941212100308
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Postoperative Vocal Function after Thyroplasty Type I and Fat Injection Laryngoplasty

Abstract: We found that MT and FIL provided almost the same effectiveness, and that both surgeries were reliable in improving the vocal function in patients with vocal fold paralysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 10 publications
(18 reference statements)
1
33
0
2
Order By: Relevance
“…All studies were published between 1998 and 2014. Six studies made comparisons between injection laryngoplasty and medialization thyroplasty (Table ) . Six studies investigated arytenoid adduction alone or with another procedure (Table ) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies were published between 1998 and 2014. Six studies made comparisons between injection laryngoplasty and medialization thyroplasty (Table ) . Six studies investigated arytenoid adduction alone or with another procedure (Table ) .…”
Section: Resultsmentioning
confidence: 99%
“…Five articles focused on acoustics and aerodynamics as primary outcome measures . All studies showed improvements in postoperative voice outcomes regardless of intervention type.…”
Section: Discussionmentioning
confidence: 96%
“…None of these studies investigate MT performed with the MTIS. One of these studies is a case series of 5 patients, in two studies, voice results in terms of acoustics and aerodynamics parameters are evaluated, the last study regards voice results in terms of voice‐related quality of life parameter . This last study concluded that “patients that were more distant from surgery had lower V‐QROL scores than those who had more recently been treated.” In other words, the only very long‐term study investigating voice results from a patients' perspective demonstrated a fading of voice results in terms of voice‐related quality of life in the course of time.…”
Section: Introductionmentioning
confidence: 99%
“…Quando comparados os resultados obtidos por injeção de gordura na prega vocal com os resultados obtidos com tireoplastias tipo 1, Umeno et al (37) não encontraram diferenças significativas entre as duas abordagens. Pelo fato da laringoplastia com injeção de gordura ser usualmente feita em centro cirúrgico e sob anestesia geral, além de ter uma taxa de absorção pouco previsível, ela não costuma ser um procedimento padrão-ouro para essa finalidade (7) .…”
Section: Resultados Obtidos Com a Il E Com As Tireoplastiasunclassified
“…Antes de analisar a necessidade de desenvolver um novo material para o uso nas IL, é pertinente questionar se os resultados funcionais conseguidos com as IL são ao menos comparáveis àqueles obtidos com a tireoplastia tipo 1. Quando comparados com a tireoplastia tipo 1, sem rotação de aritenóide, tanto a gordura quanto a HCa tiveram resultados funcionais semelhantes na correção da insuficiência glótica (37,38) .…”
Section: Delineamento Do Estudo E Metodologiaunclassified